Reconfiguration of Radial Distribution Systems: Test System - Mahdavi, Meisam [UNESP]; Siano, Pierluigi; Alhelou, Hassan Haes; Khan, Baseem (Wiley, 2021)
In modern power distribution networks, a number of remote controlled switches are allocated to provide emergency connections and for reliability improvement. Historically, distribution system reconfiguration (DSR) was initiated with the purpose of obtaining the lowest power losses. Test systems play an important role in showing efficiency of proposed models and methodologies. Nowadays, several test systems available in the specialized literature are used to verify studies regarding distribution network reconfiguration. This chapter presents different test systems, including the load data, network configuration, line characteristics, and nominal voltage. The main objective is to provide all the details and information required to evaluate methods and models developed for operation and reconfiguration of radial distribution systems. The chapter also provides important information for readers and researchers who are trying to solve the DSR problem more efficiently.